2019
DOI: 10.1017/rep.2018.24
|View full text |Cite
|
Sign up to set email alerts
|

Democracy's Deficit: The Role of Institutional Contact in Shaping non-White Political Behavior

Abstract: This paper examines the effect of institutional contact on political participation among non-White communities. While both formal and informal institutions help shape community citizen participation, their effects vary on the historical inclusion (or exclusion) of certain racial groups. Formal institutions, like political parties, have historically excluded or neglected non-White and immigrant voters. We argue that for the excluded or neglected, non-traditional political institutions, like community based orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Ramírez, Solano, and Wilcox-Archuleta (2018) find that while Asian Americans may be contacted to participate by other minorities, they are neglected by White recruiters. As an alternative to formal institutions of recruitment, community-based organizations may be more effective at recruiting Asian Americans into politics (García-Castañon et al 2019).…”
Section: Asian American Churches As Sites Of Identity Social Capitalmentioning
confidence: 99%
“…Ramírez, Solano, and Wilcox-Archuleta (2018) find that while Asian Americans may be contacted to participate by other minorities, they are neglected by White recruiters. As an alternative to formal institutions of recruitment, community-based organizations may be more effective at recruiting Asian Americans into politics (García-Castañon et al 2019).…”
Section: Asian American Churches As Sites Of Identity Social Capitalmentioning
confidence: 99%
“…The significance of the Black church to the political participation of Black communities is mirrored among immigrant groups, who rely on churches as their central socializing institution (Gordon 1964;Haddad et al 2003;Alba et al 2009). As with communities of color, immigrants suffer a dearth of attention from traditional, formal institutions such as political parties (Wong 2006;García-Castañon et al 2019), thereby increasing the ability of churches to influence immigrants' policy preferences, civic engagement, and willingness to participate politically (Gordon 1964;Jones-Correa and Leal 2001;Putnam and Campbell 2010;Djupe and Neiheisel 2012). This is because churches are trustworthy sources of information, which can be important when they do not know where else to turn for help with finding a school for their children, looking for work, or asking questions about immigration documentation (Cadge and Ecklund 2006;Cadge and Ecklund 2007;Putnam and Campbell 2010;Martinez et al 2012).…”
Section: Religion and Immigrantsmentioning
confidence: 99%
“…Congregational Social capital includes accessing the social networks of places of worship for potential goal-oriented action (Schneider 1999). Social capital is an established component to political participation; it has consistently been found that those who engage with community or volunteer organizations (including churches) have higher rates of civic and political participation (Wolfinger and Rosenstone 1980;Verba et al 1995;Tossutti 2003;García-Castañon et al 2019). It then makes sense that Putnam argues churches are the "single greatest repository of social capital" in the U.S. ( 2001), as places of worship often organize volunteer opportunities and offer prime (and ongoing) sources of both material and emotional support to members, allowing for the development of relationships and a community, which form the backbone of social capital (Manzano 2007;Brown and Brown 2003).…”
Section: Churches and Social Capitalmentioning
confidence: 99%
“…Beyond this, Asian Americans can take a more active stance in standing against institutionalized anti-Blackness and racial inequality by working to increase turnout of underrepresented non-white and immigrant voters who have been historically excluded or neglected by formal institutions designed to boost citizen participation (Garcia-Castañon et al ., 2019). Specifically, Garcia-Castañon et al .…”
Section: Moving Forwardmentioning
confidence: 99%
“…Specifically, Garcia-Castañon et al . (2019) find that contact from a non-partisan/civic or community group is substantively more important for mobilizing Latinx and Asian American voters, in contrast to conventional partisan/political institutions (e.g. political parties or campaigns), which have an overall positive effect on political participation for all voters.…”
Section: Moving Forwardmentioning
confidence: 99%